A Linear Rlation Between Curvatures and Fundamental Forms - Karagoz, Serpil (IJRDO -JOURNAL OF MATHEMATICS, 2021)
In this work, a linear relation between high order fundamental forms and curvatures was obtained by using Cayley- Hamilton theorem